The Benefits and Challenges of Using Video as A Teaching Medium at MTs Al-Hidayah: Teachers’ Perception - Annisa Maharani; Chairil Anwar Korompot; Syarifah Farahdiba (State University of Makassar, 2024)
This research aims to investigate the benefits and challenges of using video as a teaching medium: teachers’ perception. Besides, this research also attempts to identify the benefits and challenges of using video as a teaching medium. Learning media is currently needed by teachers to support the teaching and learning system in the classroom. One of the media applied is video. This study aims to determine the benefits and challenges of using videos in the teaching and learning process based on teacher perceptions. In conducting this research, researchers used qualitative methods to find out and explore more detailed information. The qualitative approach method used by the researcher was descriptive qualitative. Two English teachers were selected as participants in this study. All participants were English teachers in one of the high schools in MTs Al-Hidayah consisting of two female teachers. The researcher used interviews as the data collection instrument. There were eight findings, four advantages, and four challenges. Based on the results of the study, it can be concluded that teachers' perceptions of the use of video-based learning media are very positive. Thus, it can be concluded that the use of video-based learning media can increase teacher creativity, increase student attention, increase student motivation, and Increase learning effectiveness.Keywords—Teaching video, benefits and challenges